2011
DOI: 10.1017/s0031182011001107
|View full text |Cite
|
Sign up to set email alerts
|

Third lineage of rodent eimerians: morphology, phylogeny and re-description of Eimeria myoxi (Apicomplexa: Eimeriidae) from Eliomys quercinus (Rodentia: Gliridae)

Abstract: Coccidian oocysts from feces of 46 individuals of the garden dormouse, Eliomys quercinus (Rodentia: Gliridae), were morphologically and molecularly characterized. Both morphological and sequence data (18S rDNA and ORF 470) showed low variability, indicating that all samples represent a single species. By comparison with published morphological descriptions of coccidia from glirid rodents, we determined that the samples represent Eimeria myoxi. Molecular data suggest that this species does not fall within the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 22 publications
3
13
0
Order By: Relevance
“…Taking the number of eimerian samples from rodents and the taxonomic diversity of their hosts into account, these two clusters could be potentially envisaged as the two main evolutionary sources of rodent eimerians. The identification of a third lineage formed by Eimeria myoxi has suggested that the situation may be more complex [53]. The 26 new rodent-derived Eimeria samples added in this study further support this view.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Taking the number of eimerian samples from rodents and the taxonomic diversity of their hosts into account, these two clusters could be potentially envisaged as the two main evolutionary sources of rodent eimerians. The identification of a third lineage formed by Eimeria myoxi has suggested that the situation may be more complex [53]. The 26 new rodent-derived Eimeria samples added in this study further support this view.…”
Section: Discussionsupporting
confidence: 67%
“…The results obtained with these taxa indicate that most of the rodent eimerians fall into two unrelated host-specific lineages [50][52]. Most recently, Eimeria myoxi was found to be an exception, clustering outside these two rodent groups [53].…”
Section: Introductionmentioning
confidence: 88%
“…and Strongylidae was lower than in a study in the Bohemian Forest and Český Les Mountains, Czech Republic (Strongylidae 7.4 %, Hymenolepididae 3.7 %, Eimeria spp. 85.2 %) (Kvičerová et al 2011). This may be explained by husbandry related re-infection cycles and oocyst accumulation inside cages of the rehabilitation centre.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the role of garden dormice as vectors or reservoirs for infectious and potentially zoonotic agents, as recently reported for shrews (Bourg et al 2013, Weissenbock et al 2017, is poorly understood. In previous studies, several parasites have been investigated in garden dormice (Chute 1960, Matuschka et al 1999, Bertolino & Canestri-Trotti 2005, Kvičerová et al 2011, Libois 2016, Makarikov 2017, but serological surveys failed to detect antibodies against viruses in single trapped garden dormice collected during euthanasia (Boulanger et al 1996, Ledesma et al 2009. As clinical examinations of living individuals and correlations between health status and parasitic burden are lacking, the significance of parasites and other pathogens for the health of garden dormice is unknown.…”
Section: Clinical Examination Methods and Investigationmentioning
confidence: 99%
“…Genetic markers from nuclear (nu) and mitochondrial (mt) genomes, and less frequently of the apicoplast (ap) genome, have been used to complement morphological taxonomy with phylogenetic analyses (Hnida & Duszynski, 1999a, 1999bKvičerová, Mikeš, & Hypša, 2011;Ogedengbe, Ogedengbe, Hafeez, & Barta, 2015;Zhao & Duszynski, 2001a). Based on the assumption of host specificity of individual Eimeria species, phylogenetic analysis of nuclear small subunit ribosomal (18S) rDNA and cytochrome c oxidase I (COI) fragments supports predominant host-parasite cospeciation (Ogedengbe, El-Sherry, Ogedengbe, Chapman, & Barta, 2018).…”
Section: Introductionmentioning
confidence: 99%